Rebuilding architecture’s epistemology: KEPKA as a framework to reorient contemporary architectural development (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Contemporary architectural practice increasingly exhibits fragmented approaches in which analysis and design, as well as visual, technical, symbolic, and social aspects, are treated as separate domains. This fragmentation reveals the absence of an epistemic framework capable of maintaining traceability between architectural claims and their underlying evidence. This article addresses this epistemic gap by proposing KEPKA (Kerangka Epistemik Properti Komposisi Arsitektur) as a regulatory framework for structured architectural reflection. KEPKA is developed through a critical synthesis of architectural theories concerned with the interrelations of function, form, experience, and meaning. It emphasises the traceability of architectural claims by grounding interpretations in elements, properties, and spatial composition. Rather than functioning as a single theory, design method, or normative value system, KEPKA operates as a reflective epistemic tool applicable across issues, methods, and paradigms without interfering with scientific claims. Structured into five analytical levels, ranging from elements and compositional relations to operational and discursive meaning, KEPKA enables an assessment of the degree to which an architectural reading or design is architecturally justified. This article argues that KEPKA does not aim to verify the truth of meaning, but to ensure that meaning remains inseparable from architectural evidence, while simultaneously opening a dialogical space for engagement with diverse theoretical traditions within architectural scholarship.
Keywords: Architectural epistemology; Architectural evidence; Compositional analysis; Design justification; Function-form-meaning; KEPKA